To fast or not to fast? How food could impact on the absorption of kinase inhibitors and its economical value - Camillo Porta (Frontiers Media S.A., 2011)
Presently, cancer patients receiving oral kinase inhibitors are suggested to take the drug with an empty stomach or, in the case of drugs such as Sorafenib which are administered twice daily, at least following a lowfat meal...